ANALISIS UPAYA KEPATUHAN HUKUM DALAM MEMENUHI HAK DAN KEWAJIBAN PASIEN BPJS KESEHATAN DI RSUD UNGARAN - Jhovia Aloedya Pramana; Septo Pawelas Arso; Wulan Kusumastuti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The Government established Law Number 40 Year 2004 About SJSN and the Government also formed BPJS Healthcare on January 1, 2014. The high number of BPJS healthcare members demands Hospitals to maintain the quality while the quantity of patients was increasing, and have a potential on the issue of gap rights and obligations of patients. After Vedika (the verification of healthcare system) RSUD Ungaran does not have a special unit in handling problems related to the participant of BPJS. The purpose of this study was to analyze legal compliance efforts to fulfill the rights and obligations of BPJS Healthcare patients at RSUD Ungaran using innovation diffusion theory from Rogers. In order to completed all this, the research used qualitative methods with descriptive approach. The Data collection used In-depth Interview. The main informants were medical record staff and head of general and staffing sub-division. The triangulation informants were the head of medical record division, the PIC officer, and the head of medical services. The result of this study that was about hospital's rights and obligations and BPJS Healthcare participant with legal compliance and good law sanction, persuasion aspect is assessed from high level relative advantage, high compatibility, low complexity, high trialability, and high observability resulting in the decision of related parties to adopt the establishment of a replacement unit of the BPJS Health Center, which was renamed SIPP as a form of legal compliance efforts for the participants of BPJS patient in RSUD Ungaran and the hospital needs. In addition, there were 4 elements of innovation diffusion that is innovation, communication channels in the form of internal and external, time of planning and execution, and social system that is the party involved. The findings of the research suggested that to discuss more the adoption of legal services unit of BPJS regulator as a replacement BPJS Health center that handles all affairs concerning BPJS Healthcare.